Traumatic dissociation of the tibial insert with patellar tendon rupture after high-flex posterior-stabilized Genesis II total knee arthroplasty - Agarwala,Sanjay (2018)
ABSTRACT The authors report the first case of traumatic late dissociation of the polyethylene insert with patellar tendon rupture after total knee arthroplasty using a high-flex posterior-stabilized Genesis II prosthesis in a 60-year-old Parkinson's disease patient. Insert dislodgement has been described most commonly with mobile-bearing and cruciate-retaining TKAs. Only four cases of insert dissociation in a high-flex fixed-bearing prosthesis have been described to date. This case report paves the way to understanding the potential reasons for insert dissociation and its management strategy.